Gold Award for Tai Jia Yee - Nor Hidayah, Mohamad (2018)
Tai Jia Yee strived to do his best so he would be able to give his single mother a better life. He would always remember the advices given by his mother, Lee Whai Leng, and that spurred him to do well.